The words in my hands - Asphyxia (Novelist) (Annick Press, 2021)
Near-future Australia is controlled by Organicore, a company that produces the "perfectly balanced" synthetic meals that have all but replaced wild food, but Piper McBride, sixteen, deaf, and cued white, begins to wonder if wild food is as dangerous as Organicore's propaganda says